Determinan Stunting pada Anak Balita di Kelurahan 1 Ulu Palembang - Santi Rosalina; Heriziana Hz (Universitas Muhamadiyah Manado, 2024)
The number of stunted toddlers in the city of Palembang in 2021 will be 992 and 555 stunted toddlers in 2022. In 2023 the number of stunted toddlers will be 437 stunted toddlers. Meanwhile, the number of stunting cases at the 1 Ulu Community Health Center at the end of 2023 was 30 toddlers and in February 2024 the number of stunting toddlers was 30 toddlers (Palembang City Health Office Data, 2023). The data analysis used in this research is univariate analysis to get a picture of the distribution. and proportions of all variables studied, and bivariate analysis to determine the relationship between the independent variable and the dependent variable was carried out using the Chi Square statistical test. Multivariate analysis is used to determine the most dominant determinant factors. From the results of the Chi-Square test, it was found that the variables IMD, Exclusive Breastfeeding, LBW, Diarrhea were related to the incidence of Stunting in children under five and from the results of the multivariate analysis the variables that were significantly related to Stunting were the factors IMD, Exclusive Breastfeeding and Recurrent Diarrhea. The results of the analysis obtained (OR) from the exclusive breastfeeding variable is 6.821, meaning that children under five who do not receive exclusive breast milk have a 6.821 times risk of experiencing stunting compared to toddlers who receive exclusive breast milk. children under five, the results of the analysis obtained (OR) from the exclusive breastfeeding variable is 6.821, meaning that children under five who do not receive exclusive breast milk are 6.821 times more likely to experience stunting compared to toddlers who receive exclusive breast milk. Providing education to the community about nutrition for toddlers in the first 1000 days for preventing stunting.